Stress Response in Pathogenic Bacteria - Kidd, Stephen P (CABI, 2014)
Bacteria have an extraordinary ability to adapt to vastly diverse environmental conditions. These environments include ecological niches which experience extremes in physical and chemical conditions and these damage cell components and therefore create a stress the cell needs to overcome. Bacteria have evolved speciﬁ c systems which allow them to respond to various stresses and, in so doing, nullify or detoxify the toxic agent, as well as systems which are designed for their metabolic adaptation to these harmful conditions, thereby allowing them to grow within these environments. In the context of pathogenic bacteria, these responses have implications for bacterial survival within their diﬀ erent environmental reservoirs, as well as their passage through food and preservation processes and then, importantly, within their human host. For bacteria which can survive in humans, either as harmless or even useful commensal bacteria or as disease-causing agents, central to this survival is their ability to use the conditions of the human body as a growth environment. The physical and chemical composition varies between tissues, organs and particular anatomical niches throughout the body. For some bacteria their site of entry to the body is vastly diﬀ erent to their end-site, and indeed diﬀ erent again from the environmental reservoir in which the bacteria have existed previously. At one level, this translates to a required variation in metabolic pathways and energy generation, due to a variation in carbon and energy source (this could be the presence of sugars, carbohydrates or amino acids, or the amount of oxygen present), as well as the availability of other macro- and micronutrients that the bacteria require to survive. With some of these nutrients, the host sequesters them tightly for its own use, creating an environment of nutrient starvation for the bacteria. In addition, there are conditions created by the host speciﬁ cally to clear invading pathogens such as temperature and pH and then the presence of host-generated and damaging chemicals such as reactive oxygen and reactive nitrogen species. The interactions and combinations of these stresses generate a complex and harmful environment, which in many cases is speciﬁ c to a particular part of the body, and thereby a bacterium which inhabits an anatomical niche has evolved specialized survival mechanisms tailored for that environment. While there are recent books which deal with many of these aspects, there is not one which covers the ﬁ eld of bacterial response and adaptation to the environmental stresses within the human host.